Entrepreneurial Potential of the Russian Society: Analysis and Recommendations of How to Involve People into Small Businesses - Александр Юльевич Чепуренко (Journal of Economic Sociology, 2010)
The paper overviews the results of the study that was done by a group of authors from the Russian Independent Institute for Social and National Problems in 2002. The study was held in several Russian regions. The attitude towards small business is under focus. Proto-entrepreneurs are identified (those who are more likely to be engaged in small business), their social and demographic characteristics are given. The role of the supporting structures is also considered. The motive typologies of proto-entrepreneurs are constructed.